State of oncology nursing training and practice in a southwestern Nigerian teaching hospital (2021)
Background and objective: Oncology nursing is a recognized nursing specialty globally but it is yet to be a stand-alone specialty in any accredited degree awarding tertiary institution in Nigeria as at the time of this write up. In most of the hospitals in Nigeria, non-specialist oncology nurses who learn on the job care for the cancer patients. Hence, the urgent need to conduct this study, which aimed to examine the state of oncology nursing training and practice in Nigeria. Methods: A descriptive, cross-sectional study was used to assess 171 nurses’ socio-demographic data, nature of their oncology training, and competency level using a semi-structured questionnaire. Results: Only 3 (1.8%) of the respondents claimed they had a degree in oncology nursing and 89.9% had no formal training in oncology. Few of the respondents (13.5%) rated themselves as experts in oncology nursing practice. Majority of the respondents see the state of oncology nursing practice as very poor with the major challenge being none availability of oncology nursing training institution. Conclusions and implication for study: With the increasing prevalence of cancer in Nigeria and rise in number of new cases daily, there is need for an established programme to train health care professionals especially nurses to combat its increasing rate. There is need for provision of oncology nurse specialist training to improve level of education and skills in order to offer appropriate care to clients living with cancer and improve patient’s outcome of survival ultimately enhancing their quality of life.